Extra-conventional strengthening mechanisms in non-recrystallized grains of an extruded Mg-Gd-Zr alloy - Qiang Yang; Shuhui Lv; Kai Guan; Zefeng Xie; Xin Qiu (Journal of Magnesium and Alloys)
Mg-RE (RE = rare earth) based alloys generally exhibit outstanding mechanical properties. However, their high-strength seems to be unexplained using classic strengthening mechanisms in some cases. Herein, a Mg-13Gd-0.4Zr (wt%) alloy that was fabricated by a conventional differential thermal extrusion plus artificial aging treatment exhibits ultra-high yield strength over 510 MPa in both tension and compression. Characterizations using Cs-corrected scanning transmission electron microscopy (STEM) show two unusual microstructures in non-recrystallized grains as: a large density of basal stacking faults (SFs) and profuse distortion areas (DAs). Atomic-resolution STEM imaging indicates that basal SFs are consisted of two types of intrinsic SFs, namely I1 and I2, and DAs are self-assembled by 〈c〉 and 〈c + a〉 screw partials. Their strengthening mechanisms are analogous to grain boundary strengthening and dispersion strengthening, respectively, contributing satisfactory yield-strength increments of ∼46 MPa and ∼76 MPa, respectively. Moreover, DAs improved aging hardening by inducing novel clusters at DA-related boundaries, or increasing the number density of βH’ precipitate and promoting their distribution along a certain direction. This work supplements the strengthening mechanisms in traditional high-strength Mg-RE(-Zr) based alloys and provides novel insights in the development of ultra-high-strength Mg alloys.